LITERATURE REVIEW : THE INFLUENCE OF CAPITAL STRUCTURE, DIVIDEND POLICY,COMPANY VALUE ON PROFITABILITY: CASE STUDY OF PT. UNILEVER TBK. 2018 – 2022 - Anggraini Putri Otorus Carolina (Draf Solusi Indonesia, 2023)
This research is a literature review examiningtheinfluence of capital structure, dividend policy,company value on profitability. This research focuseson large companies in Indonesia, namely the casePT.Unilever Tbk. The period used in this research is 2018– 2022 where the research problem raised is thedecline in the company's net profit. This research willtest the influence of capital structure, dividend policy,company value on profitability using SPSS statisticaltools by testing classical assumptions and testinghypotheses with the t test and f test.